A matemática e a construção da cidadania na educação de jovens e adultos : concepções de professores que atuam no ensino médio em Cuiabá e Várzea Grande - MT - Camargo, Euguidson Jorge (2012)
When reviewing the history of the construction of the human rights, citizenship and democracy, from the struggles of social classes we see that the route of the mathematics education was no different, it goes hand in hand with the transformations that have occurred and have been turning up in space and time, as society becomes the mathematics education also evolves. In this process the society requires a population better prepared to demand their rights and duties to live in community. Thus, the present work refers to a research on the construction of citizenship with the contribution of mathematics education. We had as main objective the research of how high school teachers, youth and adult education, Airpot and Várzea Grande-MT understood the contributions of mathematics education in the construction of citizenship. We support you in the conceptions of teachers reported in speeches and planning relating to the execution of their math classes in high school in the EJA. The research was developed through a qualitative approach, interpretive nature based Bogdan and Coats (1994), Martin and Andrew (2004), Fiorentini and Leiva (2006), Triviños (2006) and others. We started the process of developing the work performing a bibliographic study with the purpose of raising the authors that discuss the subject of the search. The conceptual categories of this research were used with the intention to indicate theoretical aspects related to youth and adult education, mathematics education and education for citizenship. Our Historical conceptions of human rights and citizenship, education and youth and adult education in the perspective of the construction of citizenship, these authors: Brazil (1988, 1996), Carvalho (2011), Comparato (1992, 1999), Cortina (2005), Freire (1997, 2001, 2003, 2008), Francis (2002), Haddad e Di Pierro (2000), Jelim (1994), Marshall (1967), Ribeiro (2007), Ricaldes (2011), among others. For the construction of Mathematical Education and citizenship category deal with the authors: Weevil (2005), Brazil (1998, 2000, 2002), D'ambrosio (1993, 1994, 1996, 1998, 1999, 2001), Foster (1994, 1995) Fonseca (2002), Garnica (2004), Miorim (1998), Miguel and Miorim (2004), among others. Another part of the study consisted in a search for production of information through questionnaires, semi-structured interview and documentary analysis. The research subjects were six teachers graduates in mathematics that acted in high school, in three centers of youth and adult education in the municipalities mentioned. The analyses were performed by subject without judgment or interest to establish comparisons between the subjects involved. The results of question guideline that proposed to investigate how the high school mathematics teachers, EJA Cuiabá and Várzea Grande-MT, comprised the contribution of mathematics education in the construction of citizenship revealed that, although the EJA documents were in accordance with the current legislation which calls for Liberating perspective, the lines of investigation were transferred between the Conservative Outlook and Liberating, with a tendency to Liberating perspective.